The 2021 heatwave was less rare in Western Canada than previously thought - Elizaveta Malinina; Nathan P. Gillett (Weather and Climate Extremes, 2024)
The 2021 Pacific Northwest heatwave resulted in record temperatures observed across the Canadian provinces of British Columbia, Alberta and Saskatchewan as well as the US states of Washington and Oregon. Previous studies of extreme temperatures over arbitrarily-defined rectangular regions covering parts of Oregon, Washington and British Columbia have estimated return periods of 200–100 000 years, generally based on data since 1950, with some analyses suggesting that the event would have been considered impossible based on statistical fits to pre-2021 data, or based on climate models failing to simulate such events. We estimate a return period of 1152 (126-∞) years for the 2021 event averaged over British Columbia, based on a generalized extreme value distribution (GEV) with a location parameter a function of global mean surface temperature fitted to 1950–2021 ERA5 data. British Columbia was the province where the highest absolute temperature of 49.6 °C was measured, and where the largest impacts on human mortality and ecosystems were reported. However, we show that this return period is reduced to 236 (52-∞) years when the analysis period is extended back to 1940, using newly-available ERA5 data, owing to an extreme heatwave observed in 1941. While the 1941 event was 1.7 °C cooler than the 2021 event in British Columbia, it was a rarer event relative to the cooler climatology of the time, with an estimated return period of 735 (135-∞) years. Over this longer period we also find that almost all CMIP6 models underestimate variability in annual maximum temperatures over British Columbia. The return period of the 1941 heatwave was comparable to that of the 2021 event in Alberta and Saskatchewan, though not in Washington or Oregon. While the 2021 event was an unprecedented and extremely intense heatwave whose likelihood was much increased by human-induced climate change, our results indicate that this event was not as rare as previously thought in Western Canada.